ANALISIS HUBUNGAN MOTIVASI BELAJAR TERHADAP PRESTASI AKADEMIK SISWA SMP DARUL AKHLAQ - Margareta, Agatha Lola Margareta; Nurul Hidayah,; Arif Hidayat,; Irma Mila Karimah,; Devy Habibi Muhammad, (Rihlah Review: Jurnal Pendidikan Islam, 2025)
This study aims to examine the relationship between learning motivation—both intrinsic and extrinsic—and academic achievement among students at SMP Darul Akhlaq, Probolinggo Regency. The research employed a quantitative correlational approach involving 34 students from three grade levels in the 2024/2025 academic year. Data were collected through a Likert-scale questionnaire and academic report documentation, then analyzed using SPSS 24. Validity testing confirmed that all questionnaire items were valid, and the reliability test yielded a Cronbach’s Alpha value of 0.581, indicating acceptable reliability. Simple linear regression analysis showed an R value of 0.717 and R² of 0.514, indicating that learning motivation contributes 51.4% to variations in students’ academic achievement. These findings underscore the significant role of motivation in academic success and highlight the need for school-based interventions to create a supportive learning environment. This study offers contextual contributions by focusing on an Islamic school setting, which remains underexplored in research on this topic.